2017
DOI: 10.1139/cgj-2016-0226
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of plant growth and transpiration-induced matric suction under mixed grass–tree conditions

Abstract: Investigation of plant growth and transpiration-induced matric suction under mixed grass-tree conditions Ni, J. J.; Leung, Anthony; Ng, C. W. W.; So, P. S. General rightsCopyright and moral rights for the publications made accessible in Discovery Research Portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 64 publications
0
25
2
Order By: Relevance
“…In response to rainfall, soil water content increased correspondingly. This is contradictory to previous laboratory and field test results (Simon and Collison, 2002;Garg et al, 2015;Ni et al, 2017), which consistently showed that water content in the vegetated soil was lower than that in the bare soil. Soil water content was found to decrease after rainfall due to evaporation (E) and ET from bare and tree-covered soils, respectively.…”
Section: Interpretation Of Test Resultscontrasting
confidence: 99%
“…In response to rainfall, soil water content increased correspondingly. This is contradictory to previous laboratory and field test results (Simon and Collison, 2002;Garg et al, 2015;Ni et al, 2017), which consistently showed that water content in the vegetated soil was lower than that in the bare soil. Soil water content was found to decrease after rainfall due to evaporation (E) and ET from bare and tree-covered soils, respectively.…”
Section: Interpretation Of Test Resultscontrasting
confidence: 99%
“…Plant roots cause changes in soil matric suction (Simon & Collison, 2002;Veylon et al, 2015;Ng et al, 2016a;Ni et al, 2017) through evapotranspiration and soil hydraulic properties, including soil water retention curve (SWRC) and soil hydraulic conductivity function (SHCF). Some studies (Table 1) showed an increase in water retention capability when plant roots are present in the soil (Scanlan & Hinz, 2010;Rahardjo et al, 2014;Leung et al, 2015;Ng et al, 2016a, b;Jotisankasa & Siririrattanachat, 2017), probably because of the blockage of soil pore space by roots (Buczko et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (Table 1) showed an increase in water retention capability when plant roots are present in the soil (Scanlan & Hinz, 2010;Rahardjo et al, 2014;Leung et al, 2015;Ng et al, 2016a, b;Jotisankasa & Siririrattanachat, 2017), probably because of the blockage of soil pore space by roots (Buczko et al, 2007). However, some studies reported an opposite result Jotisankasa and Sirirattanachat, 2017), arguably because of the formation of soil cracks due to, for instances, repeated soil shrinkage, swelling and root decay and growth (Vergani & Graf, 2015;Ng et al, 2016a;Ni et al, 2017;Leung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A major benefit in the mechanical aspect of plants on slope stability is via root soil reinforcement, which is considered as an additional soil strength or root cohesion [11][12][13][14]. Plants can provide additional slope stabilization effect further through transpiration, whereby soil moisture is extracted from the ground, thus increasing the soil suction and shear strength [15][16]. The roots can also affect soil's hydraulic conductivities, soil-water retention, and infiltration capacity in several opposing ways depending on root contents and growing stage [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Plants can provide additional slope stabilization effect further through transpiration, whereby soil moisture is extracted from the ground, thus increasing the soil suction and shear strength [15][16]. The roots can also affect soil's hydraulic conductivities, soil-water retention, and infiltration capacity in several opposing ways depending on root contents and growing stage [15,17]. Active growing roots tend to decrease permeability while decaying roots can increase macrovoid content, soil permeability, and infiltration into the soil.…”
Section: Introductionmentioning
confidence: 99%